Polymer material based on dithiazolobenzothiophene structural unit and application

By introducing dithiazolenobenzothiophene structural unit into the polymer and performing structural modification, the problem of poor solubility of BDTz polymer is solved, its solubility and crystallinity are improved, and an organic solar cell with high efficiency energy conversion efficiency is achieved.

CN119661814AActive Publication Date: 2025-03-21QINGDAO INST OF BIOENERGY & BIOPROCESS TECH CHINESE ACADEMY OF SCI

Patent Information

Application Number
CN202411787022.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-21
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

Although the BDTz unit gives the polymer the advantages of high crystallinity and low energy level, it also leads to poor solubility, which is too large to separate the acceptor mixed film phase, seriously affecting the morphology of the active layer and the performance of photovoltaic devices.

Method used

Using polymer materials based on dithiazolenobenzothiophene structural units, the solubility and crystallinity of the polymer are improved by introducing appropriate groups and structural modifications, and the compatibility between the donor and the acceptor is optimized through appropriate degree of polymerization and molar ratio.

Benefits of technology

The good solubility and photoelectric properties of polymer materials are achieved, and the energy conversion efficiency of organic solar cells is improved, reaching a high efficiency of 19%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119661814A_ABST
    Figure CN119661814A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of organic photoelectricity, and particularly relates to a polymer material containing a dithiazolobenzothiophene structural unit and application of the polymer material in an organic solar cell. The polymer material has a molecular structure as shown in formula (I), and substituent groups are described in the specification. According to the invention, a dithiazolobenzothiophene unit is used as an electron withdrawing unit to be introduced into the polymer to construct a broad-band gap donor material, and the polymer material has good crystallinity and donor-acceptor compatibility at the same time, and can obtain relatively high carrier mobility and photovoltaic performance; when the material is applied to organic solar cells, the energy conversion efficiency (PCE) can exceed 19%, and the material has a good application prospect. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of organic photoelectric technology, and specifically relates to a polymer material containing dithiazolylbenzothiophene structural units and application thereof in organic solar cells. Background Art

[0002] As the third generation of solar energy technology, organic solar cells (OSCs) have important application prospects in the fields of flexible wearable portable devices and indoor photovoltaics due to their advantages such as flexibility, light weight and tunable absorption spectrum. In recent years, with the development of non-fullerene acceptor materials (NFAs), the energy conversion efficiency of binary devices has rapidly increased to more than 18%, and the efficiency of ternary devices has exceeded 20%. Compared with the rapid development of NFAs, the development of donor polymers has been relatively slow. So far, only a few donor polymers (such as PM6, D18, PBQx, etc.) have achieved high efficiencies of more than 19% in binary devices. Therefore, the development of high-performance donor polymers suitable for non-fullerene systems is an important direction to further improve the efficiency of OSCs.

[0003] In recent years, among many donor materials, donor-acceptor (DA) conjugated polymer materials containing benzodithiazole structure (BDTz) have shown excellent optoelectronic properties due to their efficient intramolecular charge transfer effect and high crystallinity brought by high number of condensed rings, and the efficiency records have continued to rise. For example, the BDTz-based donor polymer PBB1-F can effectively optimize photon capture, and the efficiency of thick-film flexible OSCs reaches 16.84% (Energy Environ. Sci., 2021, 14, 5968); then, the donor polymer PBB-Cl with BDTz as the unit has better donor-acceptor compatibility with BTP-eC9 than PM6, and the efficiency of PM6:PBB-Cl:BTP-eC9 reaches 19.04% (Adv. Mater. 2024, 36, 2312959). In addition, Itaru Osaka's research group reported a polymer of 2,3-thiophene fused ring BDTz, which achieved a binary efficiency of 15.9% (Adv. Sci. 2023, 10, 2205682); and then by adding an ester group to the acceptor unit, the binary photoelectric efficiency was increased to 17.4% (Angew. Chem. Int. Ed. 2024, e202409814). In general, BDTz-based donor polymers have high crystallinity and low energy levels, and can achieve higher photovoltaic performance in non-fullerene systems, making them a hot topic in the research of donor materials for organic solar cells.

[0004] Although the BDTz unit gives the polymer the advantages of high crystallinity and low energy level, it also causes its solubility to deteriorate and the phase separation of the donor-acceptor mixed film to be too large, which seriously affects the morphology of the active layer and the performance of the photovoltaic device. Summary of the invention

[0005] The purpose of the present invention is to provide a polymer material containing dithiazolylbenzothiophene structural units and the application of the polymer material in organic solar cells.

[0006] To achieve the above purpose, the present invention adopts the following technical solution:

[0007] A polymer material based on dithiazolylbenzothiophene structural units, the polymer material having a molecular structure as shown in formula (I):

[0008]

[0009] In the formula,

[0010] R1, R2, and R3 may be the same or different and may be selected from hydrogen, halogen, cyano, nitro, carbonyl, carboxyl, ester, hydroxyl, C1-C 20 Alkyl, C1-C 20 Alkoxy, C1-C 20 Silane groups, C1-C 20 Alkylthio, C2-C 20 Alkenyl, C2-C 20 unsubstituted or replaced by at least one C1-C 20 an alkyl-substituted amine, aryl or heteroaryl group;

[0011] A is selected from any one of the following structures:

[0012]

[0013] D is selected from any one of the following structures:

[0014]

[0015] X is H, F or Cl;

[0016] a and b may be the same or different and are natural numbers from 0 to 2, and n represents the degree of polymerization and is a natural number between 2 and 1000.

[0017] Preferably, the polymer material is of the formula:

[0018] R1, R2, and R3 may be the same or different and may be selected from hydrogen, halogen, cyano, nitro, carbonyl, carboxyl, ester, hydroxyl, C1-C 20 Alkyl, C1-C 20 Alkoxy, C1-C 20 Silane groups, C1-C 20 Alkylthio, C2-C 20 Alkenyl, C2-C 20unsubstituted or replaced by at least one C1-C 20 an alkyl-substituted amino group, a phenyl group or a thienyl group;

[0019] A is selected from any one of the following structures:

[0020]

[0021] D is selected from any one of the following structures:

[0022]

[0023] X is H, F or Cl;

[0024] a and b may be the same or different and are natural numbers from 0 to 2, and n represents the degree of polymerization and is a natural number between 2 and 1000.

[0025] Further preferably, the polymer material is of the formula:

[0026] R1, R2, and R3 may be the same or different and may be selected from hydrogen, halogen, cyano, nitro, carbonyl, carboxyl, ester, hydroxyl, C1-C 20 Alkyl, C1-C 20 Alkoxy, C1-C 20 Silane groups, C1-C 20 Alkylthio, C2-C 20 Alkenyl, C2-C 20 unsubstituted or substituted by at least one C1-C8 alkyl group, phenyl or thienyl;

[0027] A is selected from any one of the following structures:

[0028]

[0029] D is selected from any one of the following structures:

[0030]

[0031] X is H, F or Cl;

[0032] a and b may be the same or different and are natural numbers from 0 to 2, and n represents the degree of polymerization and is a natural number between 2 and 1000.

[0033] A method for preparing a polymer material based on a dithiazolylbenzothiophene structural unit comprises mixing a monomer containing a dithiazolylbenzothiophene structure with a monomer containing a unit D, and performing a polymerization reaction under the catalysis of a catalyst, and obtaining a polymer donor material having a dithiazolylbenzothiophene structure shown in formula (I) by purification and separation.

[0034] The catalyst is a palladium catalyst; the molar ratio of the monomer based on the dithiazolylbenzothiophene structure to the monomer D is equal to 1.

[0035] The polymerization reaction temperature is 80-150° C., and the solvent used is toluene and / or N,N-dimethylformamide. When toluene and N,N-dimethylformamide are mixed, the volume ratio is 0-1.

[0036] An application of the polymer material based on dithiazolylbenzothiophene structural units, and application of the polymer as an electron donor material in an organic photoelectric device.

[0037] The organic photoelectric device is an organic solar cell, an organic electroluminescent device, an organic field effect transistor, an organic detector and a photoelectric device.

[0038] The polymer material can be used as an electron donor of an organic photoelectric material and applied in an organic solar cell, with an energy conversion efficiency of 19%.

[0039] An organic solar cell device comprises a substrate, an anode, an anode modification layer, a photoactive layer, a cathode modification layer and a cathode. The photoactive layer is a film formed by mixing the polymer donor and the acceptor.

[0040] The polymer donor material and the electron acceptor material are dissolved in a solvent and coated on a conductive substrate to prepare a film, and a metal electrode is prepared on the film to obtain a corresponding photoelectric device. The mass ratio of the donor material to the electron acceptor material used is 1:0.1 to 1:10.

[0041] The solvent is at least one of o-dichlorobenzene, chlorobenzene, chloroform, tetrahydrofuran, toluene and o-xylene.

[0042] The electron acceptor material is one of organic electron acceptors such as fullerene derivatives, ITIC and its derivatives, Y6 and its derivatives, PYT and its derivatives, N2200 and its derivatives.

[0043] Compared with the prior art, the present invention has the following beneficial effects:

[0044] The invention provides a new type of polymer donor material, which has good solubility and photoelectric properties, can be used to prepare solar cells with high energy conversion efficiency, and is an excellent donor material.

[0045] (1) The preparation method provided by the present invention introduces the dithiazolylbenzothiophene structure as an electron-withdrawing unit into the polymer donor, which can synergistically obtain good crystallinity and donor-acceptor compatibility, which is conducive to obtaining relatively excellent photoelectric properties.

[0046] (2) The dithiazolylbenzothiophene-based polymer material provided by the present invention has an appropriate absorption spectrum and energy level, can be matched with a variety of receptor materials, and is applied to a variety of devices such as organic solar cells, organic photodetectors, organic light-emitting diodes, perovskite solar cells, and organic field-effect transistors. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] The technical solution of the present invention is further described below with reference to the accompanying drawings and through specific implementation methods.

[0048] Figure 1 This is the hydrogen nuclear magnetic resonance spectrum of compound 1 synthesized in Example 1 of the present invention.

[0049] Figure 2 This is the hydrogen nuclear magnetic resonance spectrum of compound 2 synthesized in Example 1 of the present invention.

[0050] Figure 3 This is the hydrogen nuclear magnetic resonance spectrum of compound 3 synthesized in Example 1 of the present invention.

[0051] Figure 4 This is the hydrogen nuclear magnetic resonance spectrum of compound 4 synthesized in Example 1 of the present invention.

[0052] Figure 5 This is the hydrogen nuclear magnetic resonance spectrum of compound 5 synthesized in Example 1 of the present invention.

[0053] Figure 6 This is the hydrogen nuclear magnetic resonance spectrum of the polymer donor P1 synthesized in Example 1 of the present invention.

[0054] Figure 7 This is the absorption spectrum of the polymer donor P1 synthesized in Example 1 of the present invention in solution and film.

[0055] Figure 8 This is the absorption spectrum of the polymer donor P2 synthesized in Example 2 of the present invention in solution and film.

[0056] Fig. 9 This is a molecular structure diagram of the device and the active layer used in Example 4 of the present invention.

[0057] Fig.10 The current-voltage (JV) curve of the organic solar cell based on the polymer donor P1 of the present invention.

[0058] Fig.11 : is the external quantum efficiency (EQE) curve of the organic solar cell based on the polymer donor P1 of the present invention. DETAILED DESCRIPTION

[0059] In order to better illustrate the present invention, the technical solution of the present invention is further illustrated by specific embodiments below, and the examples given do not limit the protection scope of the present invention:

[0060] The polymer material of the present invention introduces the dithiazolylbenzothiophene structure into the main chain of the conjugated polymer to prepare a series of novel polymer donor materials, which have the expansion of the conjugated plane and the dipole regulation to improve the interaction with the receptor molecule, which is not only conducive to improving the carrier mobility of the material, but also improves the miscibility with the receptor, reduces the static disorder of the charge transfer state at the D / A interface and the non-radiative energy loss of the device. This type of donor material has an appropriate electronic energy level and a high carrier transport performance, and the mixed film has a suitable phase separation morphology, and achieves a high energy conversion efficiency in the organic solar cell.

[0061] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.

[0062] The experimental materials, reagents, etc. used in the following experimental examples can be obtained through commercial channels or known experimental methods.

[0063] Example 1: Synthesis of polymer P1

[0064]

[0065] (1) 4,4'-dibromo-2,2'-bis(triisopropylsilyl)-5,5'-bithiazole (1.5 g), (2,5-dichlorothiophen-3-yl)trimethyltin (1.19 g), Pd(PPh3)4 (270 mg), and anhydrous DMF (30 mL) were added to a 100 mL Schlenck tube in sequence. The mixture was reacted at 110°C for 12 hours under nitrogen protection. After cooling to room temperature, 30 mL of saturated sodium chloride aqueous solution was added. The mixture was extracted three times with petroleum ether. The organic layer was evaporated under reduced pressure and passed through a silica gel column. Dichloromethane: petroleum ether (1:7) was used as the eluent to obtain a yellow oily product 1 (375 mg, yield 23%). NMR data of product 1: 1 H NMR (600MHz, CDCl3): δ6.81 (s, 1H), 1.48 (m, J = 7.5Hz, 3H), 1.41 (sept, J = 7.5Hz, 3H), 1.20-1.15 (m, 18H), 1.15-1.10 (m, 18H).

[0066] (2) 1 (370 mg), palladium acetate (11.7 mg), tricyclohexylphosphine tetrafluoroborate (38.3 mg), cesium carbonate (339 mg), and anhydrous 1,4-dioxane (10 mL) were added to a 25 mL Schlenck tube in sequence, and the reaction was carried out at 140°C under nitrogen protection overnight. After cooling to room temperature, 5 mL of saturated sodium chloride aqueous solution was added, and the mixture was extracted three times with dichloromethane. The organic layer was evaporated under reduced pressure and then passed through a silica gel column with dichloromethane: petroleum ether (1:4) as the eluent to obtain a yellow oily product 2 (137.7 mg, yield 42%). NMR data of 2: 1 HNMR (600MHz, CDCl3): δ1.50 (sept, J = 7.5Hz, 3H), 1.27-1.20 (m, 18H).

[0067] (3) 2 (130 mg), tetrabutylammonium fluoride THF solution (1M, 1.56 mL), and THF (2 mL) were added to a 25 mL single-mouth bottle in sequence, and reacted at room temperature in the dark for 10 minutes. 5 mL of water was added, and the mixture was extracted three times with chloroform. The chloroform was removed by vacuum rotary evaporation to obtain a yellow solid product 3 (62.2 mg, yield 95%). NMR data of 3: 1 H NMR (600MHz, CDCl3): δ9.08 (s, 1H).

[0068] (4) 3 (60 mg), Pd(PPh3)4 (22 mg), tributyl(4-(2-ethylhexyl)thiophen-2-yl)stannane (227 mg), anhydrous DMF (1 mL), and anhydrous toluene (1 mL) were added to a 10 mL Schlenck tube in sequence, and the reaction was carried out at 110°C under nitrogen protection overnight. After cooling to room temperature, 5 mL of saturated sodium chloride aqueous solution was added, and the mixture was extracted three times with petroleum ether. The organic layer was evaporated under reduced pressure and then passed through a silica gel column with dichloromethane: petroleum ether (1:3) as the eluent to obtain a yellow waxy product 4 (130.4 mg, yield 92%). NMR data of 4: 1 HNMR (600MHz, CDCl3): δ8.89(s,1H),7.47(s,1H),7.02(s,1H),2.62(d,J=6.7Hz,2H),1.71-1.68(m,1H),1.38-1.24(m,8H),0.99-0.79(m,6H).

[0069] (5) 4 (130 mg), NBS (55.6 mg), and chloroform (5 mL) were added to a 25 mL single-mouth bottle in sequence, and the mixture was reacted at room temperature in the dark for 4 hours. 5 mL of water was added, and the mixture was extracted three times with chloroform. The chloroform was removed by rotary evaporation under reduced pressure, and then the mixture was passed through a silica gel column with chloroform: petroleum ether (1:8) as the eluent to obtain a yellow solid product 5 (115 mg, yield 73%). NMR data of 5: 1H NMR (600MHz, CDCl3): δ7.85 (s, 1H), 6.95 (s, 1H), 2.50 (d, J = 7.2Hz, 2H), 1.72-1.69 (m, 1H), 1.40-1.20 (m, 8H), 0.95-0.80 (m, 6H).

[0070] (6) 5 (40.9 mg), FBDT-SnMe3 (42.4 mg), Pd2(dba)3 (1.3 mg), P(o-tol)3 (2.7 mg), and anhydrous TL (0.95 mL) were added to a 10 mL Schlenck tube in sequence, and the mixture was reacted at 110° C. for 24 hours under nitrogen protection. After cooling to room temperature, the reaction solution was added dropwise to 150 mL of methanol for chromatography to obtain a crude product, which was then extracted with n-hexane, dichloromethane, and chloroform, respectively. The high molecular weight component was finally collected with hot chlorobenzene and gradually dripped into methanol to obtain a purple-red solid product P1 (36.8 mg, yield 64%). NMR data of P1: 1 H NMR(600MHz, CDCl3):7.43-7.14(br),4.20-2.61(br),2.28-0.69(br).

[0071] The polymer was dissolved in chloroform and spin-coated on the surface of a quartz wafer. The thin film absorption spectrum was tested using a Hitachi U-4100 UV-Vis scanning spectrophotometer. The solution absorption spectrum was tested using chloroform as the solvent. The normalized spectrum is shown in Figure 7. The thin film absorption of the P1 polymer showed a 0-0 stacking peak higher than the 0-1 peak, indicating strong intermolecular stacking in the thin film state. At the same time, it also showed a strong aggregation peak in the solution state, indicating that P1 formed a good pre-aggregation in the solution, which was conducive to the formation of obvious phase separation when the mixed film was spin-coated.

[0072] Example 2: Synthesis of polymer P2

[0073]

[0074] (1) 5 (48.9 mg), FBDT-SnMe3 (51.4 mg), Pd2(dba)3 (1.6 mg), P(o-tol)3 (3.2 mg) and anhydrous toluene (1.05 mL) were added to a 10 mL Schlenck tube in sequence, and the mixture was reacted at 110° C. under nitrogen protection for 24 hours. After cooling to room temperature, the reaction solution was added dropwise to 150 mL of methanol for chromatography to obtain a crude product. The product was then extracted with n-hexane, dichloromethane and chloroform respectively. The high molecular weight component was finally collected by chloroform and gradually added dropwise to methanol to obtain a red solid product P2 (45.6 mg, yield 75%).

[0075] The polymer was dissolved in chloroform and spin-coated on the surface of a quartz wafer. The film absorption spectrum was tested using a Hitachi U-4100 UV-Vis scanning spectrophotometer. The solution absorption spectrum was tested using chloroform as the solvent. The normalized spectrum is shown in Figure 8. Compared with the fluorine-substituted P1 molecule, the chlorine-substituted P2 exhibits a weaker 0-0 film stacking peak and weaker solution pre-aggregation. This is due to the larger steric hindrance of the chlorine atom.

[0076] Example 3: Synthesis of polymer P3

[0077]

[0078] (1) 4,4'-dibromo-2,2'-bis(triisopropylsilyl)-5,5'-bithiazole (1.5 g), (2,5-diisooctylthiophene-3-yl)tributyltin (2.25 g), Pd(PPh3)4 (271 mg), and anhydrous DMF (30 mL) were added to a 100 mL Schlenck tube in sequence. The mixture was reacted at 110°C for 10 hours under nitrogen protection. After cooling to room temperature, 30 mL of saturated sodium chloride aqueous solution was added, and the mixture was extracted three times with petroleum ether. The organic layer was evaporated under reduced pressure and then passed through a silica gel column with dichloromethane:petroleum ether (1:7) as the eluent to obtain a yellow oily product 6 (712.6 mg, yield 35%).

[0079] (2) 6 (450 mg), palladium acetate (11.7 mg), tricyclohexylphosphine tetrafluoroborate (38.3 mg), cesium carbonate (339 mg), and anhydrous 1,4-dioxane (13 mL) were added to a 25 mL Schlenck tube in sequence. The mixture was reacted at 140°C under nitrogen protection overnight. After cooling to room temperature, 5 mL of saturated sodium chloride aqueous solution was added. The mixture was extracted three times with dichloromethane. The organic layer was evaporated under reduced pressure and then passed through a silica gel column with dichloromethane:petroleum ether (1:4) as the eluent to obtain a yellow oily product 7 (187.8 mg, yield 46%).

[0080] (3) 7 (165 mg), tetrabutylammonium fluoride THF solution (1 M, 1.56 mL), and THF (2 mL) were added in sequence to a 25 mL single-necked bottle. The mixture was reacted at room temperature in the dark for 10 min. 5 mL of water was added and the mixture was extracted three times with chloroform. The organic layer was evaporated under reduced pressure and passed through a silica gel column with dichloromethane as the eluent to obtain a yellow waxy product 8 (91.3 mg, yield 92%).

[0081] (4) 8 (236.4 mg), t-BuOK (224 mg), anhydrous THF (10 mL), and 2,3,4,5,6-pentafluoro-1-iodobenzene (323 mg) were added to a 25 mL Schlenck tube in sequence. The mixture was reacted at 0 °C for 1 hour under nitrogen protection. The mixture was heated to room temperature and stirred for 2 hours. 5 mL of water was added and the mixture was extracted three times with chloroform. The chloroform was removed by rotary evaporation under reduced pressure to obtain a yellow solid product 9 (351.2 mg, yield 97%).

[0082] (5) 9 (137.7 mg), Pd(PPh3)4 (22 mg), tributyl(thiophen-2-yl)stannane (212.7 mg), anhydrous DMF (1 mL), and anhydrous toluene (1 mL) were added to a 10 mL Schlenck tube in sequence. The mixture was reacted at 110 °C under nitrogen protection for 4 hours. After cooling to room temperature, 5 mL of saturated sodium chloride aqueous solution was added, and the mixture was extracted three times with petroleum ether. The organic layer was evaporated under reduced pressure and then passed through a silica gel column with dichloromethane:petroleum ether (1:4) as the eluent to obtain a yellow waxy product 10 (112.6 mg, yield 93%).

[0083] (6) 10 (108.3 mg), NBS (55.6 mg), and chloroform (5 mL) were added to a 25 mL single-necked bottle in sequence. The mixture was reacted at room temperature in the dark for 4 h. 5 mL of water was added and the mixture was extracted three times with chloroform. The chloroform was removed by rotary evaporation under reduced pressure and then passed through a silica gel column using chloroform: petroleum ether (1:8) as the eluent to obtain a yellow solid product 11 (109.5 mg, yield 81%).

[0084] (7) 11 (44.3 mg), FBDT-SnMe3 (52.4 mg), Pd2(dba)3 (1.5 mg), P(o-tol)3 (3.4 mg) and anhydrous toluene (0.90 mL) were added to a 10 mL Schlenck tube in sequence, and the mixture was reacted at 110°C under nitrogen protection for 24 hours. After cooling to room temperature, the reaction solution was added dropwise to 150 mL of methanol for chromatography to obtain a crude product. The product was then extracted with n-hexane, dichloromethane and chloroform, respectively. The high molecular weight component was finally collected by hot chlorobenzene and gradually added dropwise to methanol to obtain a purple-red solid product P5 (44 mg, yield 62%).

[0085] Example 4: Preparation of an organic solar cell based on donor material P1 of Example 1

[0086] The PEDOT:PSS solution was spin-coated on a clean conductive glass (ITO) substrate and heated at 150°C for 10 minutes. The thickness of the PEDOT:PSS was 30 nm. The polymer donor material P1 obtained in Example 1 and the non-fullerene acceptor material L8BO were dissolved in chloroform at a weight ratio of 1:1.4. The concentration of the solution based on the donor material P1 was 5.3 mg / mL. The solution was spin-coated on the PEDOT:PSS film as an active layer with a thickness of 100 nm. The PDINN solution was spin-coated on the active layer, and Ag was evaporated onto the surface of the PDINN with a thickness of 80 nm to obtain the organic solar cell (see Fig. 9 ). Among them, ITO (Indium Tin Oxides) is the abbreviation of indium tin oxide, which is used as the anode of the organic solar cell in the embodiment; PEDOT:PSS is an aqueous solution of a high molecular polymer, which is composed of two substances, PEDOT and PSS. PEDOT is a polymer of EDOT (3,4-ethylenedioxythiophene monomer), and PSS is polystyrene sulfonate; PDINN is the abbreviation of N,N'-bis{3-[3-(dimethylamino)propylamino]propyl}piperene-3,4,9,10-tetracarboxylic acid diimide, which is used as an electron transport layer.

[0087] The photovoltaic performance of the polymer was characterized using a Keithley 2400 Source Meter and a Xenon-lamp-based solar simulator. 2 Under the light intensity, the open circuit voltage of the photovoltaic device based on P1 is 0.901V and the short circuit current density is 27.01mA / cm 2 , the fill factor is 78.90%, the energy conversion efficiency is 19.21%, and the current-voltage curve (JV curve) of the solar cell of the corresponding device is as follows Fig.10 The external quantum efficiency spectrum was obtained by the QE-R3011 Enli Tech test system, and the integral current obtained by integrating the response curve was 25.75 mA / cm 2 , which is less than 5% of the test result of (JV curve) (see Fig.11 ).

[0088] The applicant declares that the present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A polymer material based on dithiazolylbenzothiophene structural units, characterized in that: The polymer material has a molecular structure as shown in formula (I): In the formula, R1, R2, and R3 may be the same or different and may be selected from hydrogen, halogen, cyano, nitro, carbonyl, carboxyl, ester, hydroxyl, C1-C 20 Alkyl, C1-C 20 Alkoxy, C1-C 20 Silane groups, C1-C 20 Alkylthio, C2-C 20 Alkenyl, C2-C 20 Alkynyl; unsubstituted or replaced by at least one C1-C 20 an alkyl-substituted amine, aryl or heteroaryl group; A is selected from any one of the following structures: D is selected from any one of the following structures: X is H, F or Cl; a and b may be the same or different and are natural numbers from 0 to 2, and n represents the degree of polymerization and is a natural number between 2 and 1000.

2. The polymer material based on dithiazolylbenzothiophene structural units according to claim 1, characterized in that: The polymer is of the formula, R1, R2, and R3 may be the same or different and may be selected from hydrogen, halogen, cyano, nitro, carbonyl, carboxyl, ester, hydroxyl, C1-C 20 Alkyl, C1-C 20 Alkoxy, C1-C 20 Silane groups, C1-C 20 Alkylthio, C2-C 20 Alkenyl, C2-C 20 Alkynyl; unsubstituted or replaced by at least one C1-C 20 an alkyl-substituted amino group, a phenyl group or a thienyl group; A is selected from any one of the following structures: D is selected from any one of the following structures: X is H, F or Cl; a and b may be the same or different and are natural numbers from 0 to 2, and n represents the degree of polymerization and is a natural number between 2 and 1000.

3. The polymer material based on dithiazolylbenzothiophene structural units according to claim 2, characterized in that: The polymer is of the formula, In the formula, R1, R2, and R3 may be the same or different and may be selected from hydrogen, halogen, cyano, nitro, carbonyl, carboxyl, ester, hydroxyl, C1-C 20 Alkyl, C1-C 20 Alkoxy, C1-C 20 Silane groups, C1-C 20 Alkylthio, C2-C 20 Alkenyl, C2-C 20 unsubstituted or substituted by at least one C1-C8 alkyl group, phenyl or thienyl; A is selected from any one of the following structures: D is selected from any one of the following structures: X is H, F or Cl; a and b may be the same or different and are natural numbers from 0 to 2, and n represents the degree of polymerization and is a natural number between 2 and 1000.

4. A method for preparing a polymer material based on dithiazolylbenzothiophene structural units according to claim 1, characterized in that: A monomer containing a dithiazolylbenzothiophene structure is mixed with a monomer containing a unit D, and a polymerization reaction is carried out under the catalysis of a catalyst, and a polymer donor material having a dithiazolylbenzothiophene structure shown in formula (I) is obtained by purification and separation.

5. The method for preparing a polymer material based on dithiazolylbenzothiophene structural units according to claim 4, characterized in that: The catalyst is a palladium catalyst; the molar ratio of the monomer A based on the dithiazolylbenzothiophene structure to the monomer D is equal to 1.

6. The method for preparing a polymer material based on dithiazolylbenzothiophene structural units according to claim 4, characterized in that: The polymerization reaction temperature is 80-150° C., and the solvent used is toluene and / or N,N-dimethylformamide. When toluene and N,N-dimethylformamide are mixed, the volume ratio is 0-1.

7. An application of the polymer material based on dithiazolylbenzothiophene structural units according to claim 1, characterized in that: The polymer is used as an electron donor material in an organic optoelectronic device.

8. An organic solar cell device comprising a substrate, an anode, an anode modification layer, a photoactive layer, a cathode modification layer and a cathode, characterized in that: The photoactive layer is a film formed by mixing the polymer donor and the acceptor as described in claim 1.

Citation Information

Patent Citations

  • Benzothiadiazole-based non-fullerene organic solar cell

    CN110556482A

  • Ester thiazole broad-band gap polymer and application thereof in photoelectric device

    CN113929880A

  • Bithiazole broad-band gap polymer and application thereof in photoelectric device

    CN115584017A

  • Terpolymer based on 2,5-bis(2-thienyl)thiazolo[5,4-d]thiazolyl

    US20210395442A1

  • Fused ring benzothiadiazole-based non-fullerene acceptor material, preparation method therefor and use thereof

    WO2020052194A1

Cited By

  • Ternary copolymer donor material as well as preparation method and application thereof

    CN122011342A